Modular approach toward protic N-heterocyclic carbene complexes from tosylated benzyl isocyanide metal complexes and imines - Hubbert, Christoph; Dietl, Martin C.; Zahner, David; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Organometallics, 2023)
Tosylated benzyl isocyanide complexes of gold(I), iridium(III), ruthenium(II), and rhodium(III) precursors were prepared and converted to the corresponding protic N-heterocyclic carbene (pNHC) metal complexes by reacting with imines. This modular approach offers a straightforward strategy for synthesizing pNHC-metal complexes starting from readily available imine precursors. In contrast to the common disconnection of isonitrile-based NHC complexes, which are synthesized by the addition of amines with tethered electrophiles, this approach also gives access to pNHC complexes of other catalytically relevant metals like ruthenium, rhodium, and iridium.
Online veröffentlicht: 20. September 2023
Gesehen am 23.11.2023